2017
DOI: 10.1007/s10792-017-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and morphometry of lacrimal drainage system in relation to bony landmarks in Caucasian adults: a cadaveric study

Abstract: This study provides useful anatomical and positional relationship of bony lacrimal landmarks and nasolacrimal duct in Caucasian adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…Cadaveric measurements may be more accurate than radiological measurements. However, the cadaver studies have only been conducted in a small number of elderly population samples with an unknown history of lacrimal disease [2][3][4][5]. Most radiological studies were retrospective and examined the nasolacrimal anatomy of non-PANDO subjects using conventional axial CT. 6,8−11 All previous studies, except one 12 do not consider the bias that arose by including both eyes of the same individual in their analysis [2][3][4][5][6][7][8][9][10][11][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadaveric measurements may be more accurate than radiological measurements. However, the cadaver studies have only been conducted in a small number of elderly population samples with an unknown history of lacrimal disease [2][3][4][5]. Most radiological studies were retrospective and examined the nasolacrimal anatomy of non-PANDO subjects using conventional axial CT. 6,8−11 All previous studies, except one 12 do not consider the bias that arose by including both eyes of the same individual in their analysis [2][3][4][5][6][7][8][9][10][11][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively long, horizontally inclined, or narrow canal can slow the tear ow and predispose to in ammatory obstruction. The morphology of bony NLC has been previously studied in various radiological or cadaveric studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These studies reported inconsistent results about the dimensions of the NLC and its correlations with variables such as race, age, gender, and the presence of PANDO.…”
Section: Introductionmentioning
confidence: 99%
“…The morphometry of the NLD had been a subject of numerous cadaveric studies. [4,7,[11][12][13][14] These studies aimed to evaluate morphometric properties of the NLD in different populations using cadaveric specimens. Computed tomography studies purposed determining the NLD anatomy in different patient groups such as NLD obstructions and craniofacial malformations.…”
Section: Discussionmentioning
confidence: 99%
“…The front surface of the eye is the tear film. This liquid surface looks like a slow-moving “waterfall”, which continuously moves downwards, and drains into the nasolacrimal duct and the nasal cavity [ 17 ]. The film has a unique three-layered structure.…”
Section: Ocular Barriers That Limit the Bioavailability Of Topical Drugsmentioning
confidence: 99%